Who killed Betty Gail Brown? : murder, mistrial, and mystery - Lawson, Robert G., 1938- (Lexington, Kentucky : University Press of Kentucky, 2018)
Betty Gail Brown was 19-years-old in 1961. A second-year student at Transylvania University. On the evening of October 26, she drove to campus to study with friends. Around midnight, she left the campus, but at some point she returned and parked her car in a driveway near the centre of campus. By 3:00 a.m., she was the victim of one of the most sensational killings ever to occur in the Bluegrass. She was found dead in her car. Kentuckians from across the state became engrossed in the proceedings, as lead after lead went nowhere. Four years later, the police investigation had stalled. In 1965, a drifter named Alex Arnold confessed to the killing. Arnold was brought to Lexington and put on trial, where he entered a plea of not guilty. Robert Lawson was a young attorney at a local firm when a senior member asked him to help defend Arnold. In this text, Lawson details the police search and Arnold's trial.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 9, 2018).
Keywords: Brown, Betty Gail, -- 1942-1961 -- Death; Murder victims -- Kentucky; Murder -- Kentucky; True Crime; Social services & welfare, criminology